Asymmetric Decoy State Measurement-Device-Independent Quantum Cryptographic Conferencing - 陈瑞柯 鲍皖苏 包海泽 周淳 江木生 李宏伟 (Chinese physics letters, 2017)
Measurement-device-independent quantum cryptographic conferencing （MDI-QCC） protocol suggests an important scheme for practical multiparty quantum communication. As far as we know, MDI-QCC or MDI-quantum key distribution protocols always assume that the decoy state strategies used at each user＇s side are the same. In this study, to mitigate the system complexity and to improve the performance of MDI-QCC protocol in the finite-key case, we propose an asymmetric decoy state method for MDI-QCC protocol, and present security analysis and numerical simulations. From numerical simulations, our protocol can achieve better performance in the finite-key case. That is, with a finite data size of 10111011, it can achieve nonzero secret key rate over 43.6km.